2014
DOI: 10.1111/den.12384
|View full text |Cite
|
Sign up to set email alerts
|

Emergency double‐balloon enteroscopy combined with real‐time viewing of capsule endoscopy: A feasible combined approach in acute overt‐obscure gastrointestinal bleeding?

Abstract: Emergency DBE is feasible, safe and effective in acute OGIB and may avoid major surgery, diagnosing and successfully treating most patients. Combined approach with RT viewing by CE is especially useful to identify recurrent bleeding vascular lesions such as DL that may be easily misdiagnosed by non-emergency DBE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 17 publications
(19 reference statements)
1
18
0
Order By: Relevance
“…(3,6,8) Moreover, the rebleeding rate in OGIB is significantly higher in patients with small bowel vascular lesions compared to other small bowel lesions (9,10). Even though the development of capsule endoscopy (CE) and DAE has led to an increased knowledge of angioectasias located in the small bowel, little is known about the efficacy endoscopic treatment in these lesions (9,10,13,14). The global rebleeding rate of small bowel vascular lesions (SBVL) after one endoscopic therapeutic session with DAE is 40% (9).…”
Section: Introductionmentioning
confidence: 99%
“…(3,6,8) Moreover, the rebleeding rate in OGIB is significantly higher in patients with small bowel vascular lesions compared to other small bowel lesions (9,10). Even though the development of capsule endoscopy (CE) and DAE has led to an increased knowledge of angioectasias located in the small bowel, little is known about the efficacy endoscopic treatment in these lesions (9,10,13,14). The global rebleeding rate of small bowel vascular lesions (SBVL) after one endoscopic therapeutic session with DAE is 40% (9).…”
Section: Introductionmentioning
confidence: 99%
“…BE is also useful in the case of patients who show negative results on CE examination [13]. A recent study showed that emergency DBE combined with real-time viewing with CE is useful in the case of patients with acute overt OGIB [14]. This technique facilitated the detection of recurrent vascular lesions, such as Dieulafoy’s lesions, which are easily overlooked on elective DBE.…”
Section: Negative Results Of Ce and Acute Overt Ogibmentioning
confidence: 99%
“…The therapeutic yield of DAE performed in the overt-OGIB setting ranges from 41.4 to 88.9% [14,[16][17][18][19][20][21]. Therapeutic procedures vary according to the etiology and include clipping, argon plasma coagulation, epinephrine injection, heater probe coagulation and polypectomy [14,18,[21][22][23][24].…”
Section: Small Bowel Bleedingmentioning
confidence: 99%
“…Previous findings from imaging studies or CE have a major role guiding further approach [5,12,14,28,[30][31][32][33]. If a lesion detected on CE is within the first 75% of SB transit time, an anterograde approach should be chosen [14,17,20,22,24,25,34]. Pérez-Cuadrado Robles E et al concluded that real-time CE findings can also be useful to decide the initial route on emergent SBB [17].…”
Section: Small Bowel Bleedingmentioning
confidence: 99%